Probabilistic safety assessment (PSA) of a safety critical system: a case study of a nuclear power plant - Kumar, Vinay; Pratihar, Dewanshu; Kumar Tripathi, Anil (International Journal of Engineering and Technology, 2018)
Probabilistic Safety Assessment approach has been successfully applied in engineering, economics, computer science and statistics to re-solve a wide range of safety-related problems. However, using Probabilistic Safety Assessment for quantifying safety of a safety critical system is a challenging task in Safety Engineering community. This method plays an essential role in analyzing safety of safety critical sys-tems and its various components. Therefore, in this paper, we present Probabilistic Safety Assessment framework which can be used to quantify the critical failures of a systems. The approach is well demonstrated on a Digital Feed Water Control System uses in a Nuclear Power Plant as safety critical system.Â